Methodological Advances in Experimental Philosophy 2019
DOI: 10.5040/9781350069022.ch-011
|View full text |Cite
|
Sign up to set email alerts
|

History of Philosophy in Ones and Zeros

Abstract: You will be contacted as soon as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Furthermore, philosophical writing is often precise and terminology tends to be defined or at least discussed in the text, so there should be enough information for modeling meaning even when working with small data, for instance in one or multiple works by a particular philosopher or from a particular philosophical tradition. Last but not least, the field of philosophy could benefit from this type of modeling -although philosophers have not yet made broad use of computational methods (Betti et al, 2019), it has been shown that new insights can be obtained using an information retrieval tool based on a distributional semantic model of digitalized philosophical texts (Ginammi et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, philosophical writing is often precise and terminology tends to be defined or at least discussed in the text, so there should be enough information for modeling meaning even when working with small data, for instance in one or multiple works by a particular philosopher or from a particular philosophical tradition. Last but not least, the field of philosophy could benefit from this type of modeling -although philosophers have not yet made broad use of computational methods (Betti et al, 2019), it has been shown that new insights can be obtained using an information retrieval tool based on a distributional semantic model of digitalized philosophical texts (Ginammi et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…1 For other works on the history of philosophy through topic modeling, see those of Betti and van den Berg and colleagues (Betti and van den Berg 2014;Betti and van den Berg 2016;Betti, van den Berg, Oortwijn, and Treijtel 2019) and the other contributions to the second part of Fischer and Curtis (2019).…”
Section: Journal and Year Selectionmentioning
confidence: 99%
“…In this sense, a model is both a descriptive and a heuristic device used to capture a certain feature observed in the data and support further exploration and interpretation of it. The use of the model approach in the field of history of philosophy and ideas has so far been limited to implementations in which the researcher designs the model before analyzing the data and then uses it as a heuristic tool to study a given corpus and investigate a given research question (De Jong and Betti 2010;van den Berg 2014, 2016;Betti et al 2019;Sangiacomo 2019). In this article, we experiment with the opposite approach by distilling from the structural aspects revealed by network analysis those features that seem more promising in profiling different kinds of authors and pointing to a general pattern or trend at work in the network itself.…”
Section: Canonical and Noncanonical Authorsmentioning
confidence: 99%